2021
DOI: 10.1111/and.14215
|View full text |Cite
|
Sign up to set email alerts
|

Do environmental and occupational exposure to pyrethroids and organophosphates affect human semen parameters? Results of a systematic review and meta‐analysis

Abstract: Infertility is characterised by the inability to conceive a pregnancy after at least one year of unprotected intercourse (Louis et al., 2013). This clinical condition affects up to 15% of couples (Louis et al., 2013) and, in about 40% of them, the origin is attributable to males (Bhasin et al., 1994). In approximately 31% of cases, infertility is found to be secondary and, therefore, a preventable condition (WHO, 1992).Although it is difficult to demonstrate a definitive correlation between such risk factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
(90 reference statements)
1
12
0
Order By: Relevance
“…In the present study, a significant increase in abnormal sperm morphology was found in exposed men, and a significant negative correlation was detected between this parameter and semen PYRs/3-BPA (except cypermethrin) levels. The meta-analysis study by Giulioni et al (2021) reported that morphology is the only parameter affected by PYRs exposure which also supported our study.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, a significant increase in abnormal sperm morphology was found in exposed men, and a significant negative correlation was detected between this parameter and semen PYRs/3-BPA (except cypermethrin) levels. The meta-analysis study by Giulioni et al (2021) reported that morphology is the only parameter affected by PYRs exposure which also supported our study.…”
Section: Discussionsupporting
confidence: 91%
“…OPs have also shown a worsening impact on fertility, altering the regular function of the blood–testis barrier in mice through oxidative stress, 82 forming covalent bonds with the zonula occludens‐2 protein (ZO2) 83 . The effect of OPs on semen quality emerged through a recent meta‐analysis, where we demonstrated a decline in almost all parameters considered 84 . In 11 out of the 13 studies included in this review, sperm quality was significantly affected, and the most frequently affected parameters were sperm total count (in three out of 11 studies), ejaculate volume and (in four out of 11 studies), sperm morphology and concentration (in five out of 11 studies), and motility (in seven out of 11 studies).…”
Section: Discussionmentioning
confidence: 83%
“…83 The effect of OPs on semen quality emerged through a recent meta-analysis, where we demonstrated a decline in almost all parameters considered. 84 In 11 out of the 13 studies included in this review, sperm quality was significantly affected, and the most frequently affected parameters were sperm total count (in three out of 11 studies), ejaculate volume and (in four out of 11 studies), sperm morphology and concentration (in five out of 11 studies), and motility (in seven out of 11 studies). Semen motility and morphology were the most frequently affected parameters.…”
Section: Discussionmentioning
confidence: 94%
“…88 The most recent meta-analysis revealed that occupational or environmental exposure to lead was associated with reduced semen volume, sperm count, concentration, and motility. 89 Zinc and copper are classified as essential heavy metals. Meta-analyses show reduced seminal zinc levels among men with low fertility.…”
Section: Use Of Marijuanamentioning
confidence: 99%